Formulasi Granul Effervescent Ekstrak Pandan Laut (Pandanus tectorius Parkinson ex Du Roi) Sebagai Analgetik - Sriarumtias, Framesti Frisma (Fakultas Farmasi Universitas Halu Oleo, 2020)
Sea pandanus plants are plants that are spread along the coast in Indonesia. Pandan sea fruit itself has never been used by the community, so it becomes waste on the beach. The purpose of this study was to make a formulation of effervescent granules from ethanolic extracts of sea pandanus (Pandanus tectorius) which has analgesic activity. The effervescent granule formula consists of ethanol extracts of sea pandanus, sodium bicarbonate, citric acid, tartaric acid, mannitol, lactose, PVP, aerosils and orange dyes. The difference of the three formulas are the ratio of the concentration of sodium bicarbonate which is 25%, 30% and 35%, respectively. The results show that the best formula is formula I, which fulfills the organoleptic test requirements, water content, rest angle, real specific gravity test, incompressible density test, compressibility, disperse time and pH. The analgesic activity test results using siegmund method known analgesic activity of formula I as the best formula with a dose of 125 mg / kg BW and aspirin as a comparison with a dose of 65 mg / kg body weight gives an anlgetic effect with protective power is 83.68%.